Update of genetic susceptibility in patients with Kawasaki disease - Kyung Lim Yoon (Korean Pediatric Society, 2015)
Kawasaki disease (KD) is an acute systemic vasculitis that predominantly affects children, and can result in coronary artery lesions (CAL). A patient with KD who is resistant to treatment with intravenous immunoglobulin (IVIG) has a higher risk of developing CAL. Incomplete KD has increased in prevalence in recent years, and is another risk factor for the development of CAL. Although the pathogenesis of KD remains unclear, there has been increasing evidence for the role of genetic susceptibility to the disease since it was discovered in 1967. We retrospectively reviewed previous genetic research for known susceptibility genes in the pathogenesis of KD, IVIG resistance, and the development of CAL. This review revealed numerous potential susceptibility genes including genetic polymorphisms of ITPKC, CASP3, the transforming growth factor-β signaling pathway, B lymphoid tyrosine kinase, FCGR2A, KCNN2, and other genes, an imbalance of Th17/Treg, and a range of suggested future treatment options. The results of genetic research may improve our understanding of the pathogenesis of KD, and aid in the discovery of new treatment modalities for high-risk patients with KD.